Implementasi Media Gambar dalam Mengatasi Kesulitan Belajar Membaca Siswa Kelas 1 MI Nurussyifa Timbanuh Kec. Pringgasela - Wawanmulyadi Purnama (Al-mujahidah, 2020)
This study aims to determine how image media can overcome the difficulties of learning to read in grade 1 MI Nurussyifa 'Timbanuh, Pringgasela District, East Lombok. The variables that are the target of change in this study are overcoming the difficulties of learning to read in grade 1 students of MI Nurussyifa' Timbanuh, while the variables The action or treatment used is image media. This study is a qualitative research taking the background of class 1 MI Nurussyifa 'Timbanuh, Pengambangan Village, Pringgasela District. This research was conducted by conducting observations, interviews, and documentation. The results of this study indicate: the Indonesian language learning process in Initially, MI Nurussyifa 'Timbanuh was still conventional, students learned to read through imitating sounds pronounced by the teacher so that students experienced reading difficulties. This is overcome through learning assisted with image media, because image media is more concrete about the teaching material received by students. With the implementation of image media, the difficulty of learning to read students of MI Nurussyifa 'Timbanuh can be resolved, as evidenced by the results of observations of student enthusiasm are increasingly visible, interviews with the principal and grade 1 teachers state that image media is very helpful in overcoming students' learning difficulties and appears in the documentation of research results that researchers have done